The role of non-coding RNAs miR-98, miR-19a and lncRNA MALAT1 and oxidative stress in the pathogenesis of food allergy - Erboğa, Hülya; Şahiner, Ümit Murat; Ünsal, Hilal; Soyer, Özge U.; Şekerel, Bülent E.; Birben, Esra (The Turkish Journal of Pediatrics, 2025)
Background. Food allergy is a public health concern affecting quality of life and increasing in prevalence. Numerous studies suggest that the rapid increase in the prevalence of allergic diseases may be linked to epigenetic mechanisms, particularly microRNA (miRNA), long non-coding RNA (lncRNA). The aim of this study was to investigate the effects of oxidative stress and selected non-coding RNAs on the development and pathogenesis of food allergy.Methods. A total of 26 children with food allergy and 30 healthy children were enrolled in this study. Real-time polymerase chain reaction (RT-PCR) was performed to detect the expressions of serum miR-19a, miR-98 and lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) in all the participants. Serum levels of interleukin-4 (IL-4), IL-10, IL-13 and transforming growth factor beta (TGF-β), along with levels of oxidative stress markers 8-isoprostane and cysteinyl leukotrienes, were measured by enzyme-linked immunosorbent assay.Results. Our study found that the expression of miR-98 was significantly lower in children with food allergies compared to healthy controls (p < 0.05), whereas there was no significant difference in the expression levels of miR-19a between the two groups (p > 0.05). There was no difference in gene expression levels (p > 0.05) of lncRNA MALAT1 between children with food allergies and healthy children. TGF-β levels of healthy children were found to be significantly higher than those of children with food allergies (p < 0.05). There was no statistical difference in cysteinyl leukotriene levels between patients and controls (p = 0.804). However, 8-isoprostane levels were significantly lower in patients (6.68 pg/mL; interquartile range [IQR]: 1.57-26.55) compared to controls (37.20 pg/mL, IQR: 18.55-167.58) (p < 0.001).Conclusions. Considering our findings in conjunction with existing literature, miR-98 appears to be a promising candidate biomarker for food allergy.
Keywords: epigenetics; food allergy; lncRNA MALAT1; miR-98; miR-19a; oxidative stress